2023
DOI: 10.1186/s12885-023-10577-z
|View full text |Cite
|
Sign up to set email alerts
|

High resolution dermal ultrasound (US) combined with superficial radiation therapy (SRT) versus non-image guided SRT or external beam radiotherapy (XRT) in early-stage epithelial cancer: a comparison of studies

Abstract: Background To compare the effectiveness of high-resolution dermal ultrasound (US) guided superficial radiotherapy (SRT) to non-image-guided radiotherapy in the treatment of early-stage Non-Melanoma Skin Cancer (NMSC). Methods A high-resolution dermal ultrasound (US) image guided form of superficial radiation therapy (designated here as US-SRT) was developed in 2013 where the tumor configuration and depth can be visualized prior to, during, and subs… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 18 publications
2
13
0
Order By: Relevance
“…Almost all lesions had minimal or mild toxicity scores (RTOG 0, 1, 2). Our updated results support that IGSRT, with longer follow-up, continue to offer a high local control rate felt to be comparable to the best surgical techniques (14) (15) and continues to be an effective noninvasive, non-surgical treatment modality for NMSC with its major advantages of avoiding the pitfalls of surgery clinically, cosmetically, physiologically and psychologically. These updated results validate our prior statement that IGSRT should be a primary non-surgical option presented to patients for treatment of their early-stage NMSC lesions.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Almost all lesions had minimal or mild toxicity scores (RTOG 0, 1, 2). Our updated results support that IGSRT, with longer follow-up, continue to offer a high local control rate felt to be comparable to the best surgical techniques (14) (15) and continues to be an effective noninvasive, non-surgical treatment modality for NMSC with its major advantages of avoiding the pitfalls of surgery clinically, cosmetically, physiologically and psychologically. These updated results validate our prior statement that IGSRT should be a primary non-surgical option presented to patients for treatment of their early-stage NMSC lesions.…”
Section: Discussionsupporting
confidence: 60%
“…Two recent studies, a metanalysis and a logistic regression analysis, compared IGSRT studies to large well run SRT/XRT studies without image guidance. Both analyses found that the LC rates for the IGSRT studies were statistically superior to the non-image-guided SRT/XRT studies (14), (15). The image-guided component of SRT utilizes a 22 megahertz (MHz) dermal ultrasound with color doppler to visualize the superficial depth of the skin.…”
Section: Discussionmentioning
confidence: 99%
“…Yu et al. reported 99.3% cure of cutaneous squamous cell carcinoma (SCC) and basal cell carcinoma (BCC) utilizing IG‐SRT in a study of 2917 patients 5,6 . Furthermore, Zemtsov while proposing Appropriate Use Criteria (AUC) for SRT emphasized in his recommendations the importance of utilization of HFUS while performing SRT 7 .…”
Section: Introductionmentioning
confidence: 99%
“…With the development of high‐frequency ultrasound (HFUS), the resolution is continuously improving, thus dermatological lesions can be well evaluated 21–23 . In evaluation of skin subcutaneous lesions, HFUS is now used for image guided superficial radiation therapy and Doppler modality is starting to be utilized in evaluation of vasculature of all skin lesions 24–26 …”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23] In evaluation of skin subcutaneous lesions, HFUS is now used for image guided superficial radiation therapy and Doppler modality is starting to be utilized in evaluation of vasculature of all skin lesions. [24][25][26] It should be noted that, so far as we know, most of the previous studies regarding the usefulness of HFUS were with a visible change of appearance. The appearance of lesions can provide additional diagnostic information.…”
Section: Introductionmentioning
confidence: 99%